A search of new samples of active galactic nuclei with low-mass black holes from SDSS. Issue Volume 10:Issue S312(2014) (7th March 2016) - Liu, H.; Yuan, W.; Zhou, H.; Dong, X.-B.
Abstract: We report on the progress of our on-going work to search for low-mass black holes (LMBHs) in active galactic nuclei. The masses of black holes are estimated using the broad line width and luminosity obtained from one-epoch optical spectra. As the first step, we fitted the spectra of 1263 objects in the quasar catalog of the SDSS DR10 and obtained accurate measurement of the emission lines. Two AGNs are found to have M BH 10 6 M⊙ . The next step is to analyze the spectra of the DR10 galaxy sample, from which a much larger sample of low-mass AGNs is expected to be obtained.